Health technology assessment: Choice between a cytotoxic safety cabinet and an isolator for oncology drug reconstitution in Tunisia. (July 2021) - Boufaied, Manel; Bouhlel, Mehdi; Soussi, Mohamed Ali; Lazreg, Olfa; Khrouf, Myriam Razgallah
Introduction: In order to implement a centralized cytotoxic reconstitution unit (CCRU), a study was conducted to compare the implementation costs of a CCRU equipped with a cytotoxic safety cabinet (CSC) and one equipped with an isolator with negative pressure. Materials and methods: This study compares items such as infrastructure, air treatment and CCRU qualification costs, equipment's purchase and qualifications costs, as well as staff dressing costs. Two plans were elaborated according to the international recommendations in a way that they respond to the necessary requirements in both cases. Requests for quotes for the compared items were sent to different suppliers. Results: The implementations' cost of a CCRU equipped with a CSC is cheaper than the one equipped with an isolator. The price of an isolator is much higher than a CSC; its qualification is also more expensive. However, the requirements and the costs for the air treatment and the dressing of the staff are less in the case of an isolator. The overall cost of the CCRU's implementation is approximately 1.3 times higher in the case of an isolator. However, by excluding the equipment purchase cost, the overall cost of a CSC's implementation becomes higher. Conclusion: For Tunisia, it seems that the CSC is the most adapted. However, this work should be completed by the comparison of the CCRU's operating costs in order to optimize the resources and figure out the cheapest system.